All the old knives [large type] - Steinhauer, Olen (Wheeler Publishing, 2015)
"Nine years ago, terrorists hijacked a plane in Vienna. Somehow, a rescue attempt staged from the inside went terribly wrong and everyone on board was killed. Members of the CIA stationed in Vienna during that time were witness to this terrible tragedy, gathering intel from their sources during those tense hours, assimilating facts from the ground with a series of texts coming from one of their agents inside the plane. So when it all went wrong, the question had to be asked: Had their agent been compromised, and how? Two of those agents, Henry Pelham and Celia Harrison, were lovers at the time, and in fact that was the last night they spent together. Until now. That night Celia decided she'd had enough; she left the agency, married and had children, and is living an ordinary life in the suburbs. Henry is still an analyst, and has traveled to California to see her one more time, to relive the past, maybe, or to put it behind him once and for all. But neither of them can forget that long-ago question: Had their agent been compromised, and how? And each of them also wonders what role tonight's dinner companion might have played in the way things unfolded. All the Old Knives is Olen Steinhauer's most intimate, most cerebral, and most shocking novel to date from the New York Times bestselling author deemed by many to be John le Carré's heir apparent"--Publisher.